Directive Illocutionary Act in Waves Movie - Made Shelpy Krismita Sanjaya; Gek Wulan Novi Utami; Ayu Gede Sosiowati (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The objective of this research is to identify the types of directive illocutionary acts and the meaning of the utterances produced by all the characters in the Waves movie. The present study employed a qualitative approach. The data for this study were derived from the Waves movie script, which served as the primary data source. The documentation and observation methods are employed to collect data from the movie script and the movie itself. The method of data analysis employed is qualitative analysis. The data was presented informally. The present study employs two theories to resolve two research problems. The first theory is the types of directive illocutionary acts theory by Bach and Harnish. The second theory is the aspect of speech situation by Leech. The results of the study revealed the presence of 37 directive utterances, covering all six directive types: requestives, questions, requirements, prohibitives, permissives, and advisories. The analysis indicated that the directive type of requirements was the most prevalent.